Difficulty in Diagnosing of Renal Choriocarcinoma: Case Report - Daniela Angerame Yela; Marcelo Faber; Amanda Dantas; Cristina Laguna Benetti-pinto; Rodrigo Jales (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Choriocarcinoma is a rare highly malignant tumor. We report a case of 35-year-old woman, with a history of four months menstrual irregularity and human chorionic gonadotropin persistently positive that presented transvaginal ultrasound normal and the computed tomography scan of the chest showed three nodules and abdominal scan evinced a hypervascularized solid nodular lesion on left kidney. An ultrasound-guided biopsy of left kidney was performed with a pathologic diagnosis of renal choriocarcinoma. After chemotherapy the human chorionic gonadotropin was negative and the patient returned to normal menstrual cicles.